Employers’ Expectation and Satisfaction of Open and Distance Learning Graduates - Latifah Abdol Latif; Thirumeni Subramaniam (ASEAN Journal of Open and Distance Learning, 2015)
In this new age of globalization, human capital investment is crucial in preparing a workforce that meets the rapidly changing industry needs. There is now a critical need to re-examine the function of Open University Malaysia as a higher education provider which provides opportunities for the further re-skilling and up-skilling of people who are already employed. Open University Malaysia is able to contribute significantly to lifelong learning efforts for these working adults, however, these institutions have constantly been regarded as ‘the lower quality alternative’ with their flexible entry policy and flexible delivery and learning modes. This paper examines the extent to which Open University Malaysia, the country's premier ODL university trains and develops its graduates to meet employers' expectations with regard to the different types of skills required at the workplace. Printed questionnaires were sent via postal mail to employers of the December 2013 graduates of the Bachelor degree programmes. Responses of 109 out of a total of 600 (18.2%) employers were analysed using quadrant and gap analysis for four dimensions of employability skills namely, Knowledge and Understanding, General Qualities, General Skills and Specialized Skills. Quadrant analysis indicates that General Qualities fall in the strength quadrant, followed by General Skills, but to a lesser extent. Specialized Skills and Knowledge and Understanding were placed in the low priority quadrant. In the overall evaluation, 90.8% of employers were “satisfied” and “very satisfied” with employee’s knowledge and skills; 59.6% indicated that general performance of the OUM graduates are “better” and “much better” compared to others and 89.0% are likely to employ graduates from OUM. The positive findings serve as evidence on the success of OUM in fulfilling its role in enhancing general qualities and skills that are synonymous to lifelong learning skills expected by employers. [ABSTRACT BY AUTHORS]